STRUCTURAL INSIGHTS INTO THE ROLES OF SEQA ON ORIGIN SEQUESTRATION AND CHROMOSOME ORGANIZATION - Chung, Yu Seon (My University, 2011)
DNA replication is a fundamental process that must be precisely regulated to ensure timely and faithful transmission of genetic material for proliferation of all organisms. Replication initiation is regulated through a series of precisely timed protein–DNA and protein–protein interactions. In Escherichia coli, one regulatory mechanism of replication initiation occurs through SeqA binding to specific sequences within the oriC, resulting in origin sequestration. SeqA also plays a role in chromosome organization at the replication forks. Despite the functional importance of SeqA in E. coli, its DNA binding mechanism has remained elusive. The work described in this thesis has shown for the first time the minimal functional unit of SeqA that forms a high-affinity complex with DNA through the loss of symmetry. This is a novel observation that explains how SeqA can distinguish template versus newly replicated strand of DNA. We have also identified a protein–protein interaction surface that separates the roles of SeqA at the origin in sequestration and at the replication forks in chromosome organization. The final contribution of the thesis is in the exploration of SeqA functions in other bacterial species and demonstrating the structural and functional similarities between Vibrio cholerae SeqA and E. coli SeqA. Together our work has made a crucial connection between the structural organization of the protein and its functional ability to bind DNA.
Keywords: E. coli DNA replication; negative regulator; DNA binding protein; SeqA; chromosome organization; Biochemistry; Structural Biology; Biochemistry